On collegial deliberation as a tool to counteract racism in education - Andreas Bergh; Tomas Englund (Education Inquiry)
This paper analyses and discusses the possibilities and challenges of collegial mutual deliberation among teachers as a way of counteracting racism. It takes its starting point in research on teacher collaboration that emphasises the importance of creating conditions locally for critical discussions, building on knowledge from different perspectives and going beyond simple solutions. With a focus on the practical, the idea of deliberative communication serves as a theoretical lens to analyse discussions among eight teachers on their responses to racism. The study provides theoretical and empirical knowledge about the potential contribution of collegial deliberation to developing a communicative teacher community that counteracts racism.